Rope trauma, sedation, disentanglement, and monitoring‐tag associated lesions in a terminally entangled North Atlantic right whale (Eubalaena glacialis). Issue 2 (28th August 2012) - Moore, Michael; Andrews, Russel; Austin, Trevor; Bailey, James; Costidis, Alex; George, Clay; Jackson, Katie; Pitchford, Tom; Landry, Scott; Ligon, Allan; McLellan, William; Morin, David; et al.
Abstract A chronically entangled North Atlantic right whale, with consequent emaciation was sedated, disentangled to the extent possible, administered antibiotics, and satellite tag tracked for six subsequent days. It was found dead 11 d after the tag ceased transmission. Chronic constrictive deep rope lacerations and emaciation were found to be the proximate cause of death, which may have ultimately involved shark predation. A broadhead cutter and a spring‐loaded knife used for disentanglement were found to induce moderate wounds to the skin and blubber. The telemetry tag, with two barbed shafts partially penetrating the blubber was shed, leaving barbs embedded with localized histological reaction. One of four darts administered shed the barrel, but the needle was found postmortem in the whale with an 80º bend at the blubber‐muscle interface. This bend occurred due to epaxial muscle movement relative to the overlying blubber, with resultant necrosis and cavitation of underlying muscle. This suggests that rigid, implanted devices that span the cetacean blubber muscle interface, where the muscle moves relative to the blubber, could have secondary health impacts. Thus we encourage efforts to develop new tag telemetry systems that do not penetrate the subdermal sheath, but still remain attached for many months.